Exploring the Genotype–Phenotype Correlation in GBA-Parkinson Disease: Clinical Aspects, Biomarkers, and Potential Modifiers - Menozzi, Elisa; Schapira, Anthony H. V. (Frontiers in Neurology, 2021)
Variants in the glucocerebrosidase (GBA) gene are the most common genetic risk factor for Parkinson disease. These include pathogenic variants causing Gaucher disease (divided into ‘severe’, ‘mild’, or ‘complex’-resulting from recombinant alleles-based on the phenotypic effects in Gaucher disease) and ‘risk’ variants which are not associated with Gaucher disease but nevertheless confer increased risk of Parkinson disease. As a group, GBA-Parkinson disease patients have more severe motor and nonmotor symptoms, faster disease progression, and reduced survival compared with non-carriers. However, different GBA variants impact variably on clinical phenotype. In the heterozygous state, ‘complex’ and ‘severe’ variants are associated with a more aggressive and rapidly progressive disease. Conversely, ‘mild’ and ‘risk’ variants portend a more benign course. Homozygous or compound heterozygous carriers usually display severe phenotypes, akin to heterozygous ‘complex’ or ‘severe’ variants carriers. This article reviews genotype-phenotype correlations in GBA-Parkinson disease, focusing on clinical and non-clinical aspects (neuroimaging and biochemical markers), and explores other disease modifiers that deserve consideration in the characterisation of these patients.